A Vietnamese royal exile in Japan : Prince Cuong De (1882-1951) - Tran, My-Van (Routledge studies in the modern history of Asia ;, 2005)
Prince Cuong De, viewed by the French as a pretender to the Vietnamese throne, was an important and interesting figure in the history of Vietnam's struggle for independence. He was highly regarded by many non-communist Vietnamese nationalists, but has been virtually 'written out' of Vietnamese history. Based on extensive original research, including interviews and important documents from the French national archives, this book traces the life of Cuong De as a royal exile in Japan, exploring his links to key Japanese leaders and how he campaigned for his cause and was supporte.